Validating novel tau positron emission tomography tracer [F‐18]‐AV‐1451 (T807) on postmortem brain tissue. Issue 5 (25th September 2015) - Marquié, Marta; Normandin, Marc D.; Vanderburg, Charles R.; Costantino, Isabel M.; Bien, Elizabeth A.; Rycyna, Lisa G.; Klunk, William E.; Mathis, Chester A.; Ikonomovic, Milos D.; Debnath, Manik L.; Vasdev, Neil; Dickerson, Bradford C.; et al.
<x xml:space="preserve">Abstract</x> Objective To examine region‐ and substrate‐specific autoradiographic and in vitro binding patterns of positron emission tomography tracer [F‐18]‐AV‐1451 (previously known as T807), tailored to allow in vivo detection of paired helical filament‐tau–containing lesions, and to determine whether there is off‐target binding to other amyloid/non‐amyloid proteins. Methods We applied [F‐18]‐AV‐1451 phosphor screen autoradiography, [F‐18]‐AV‐1451 nuclear emulsion autoradiography, and [H‐3]‐AV‐1451 in vitro binding assays to the study of postmortem samples from patients with a definite pathological diagnosis of Alzheimer disease, frontotemporal lobar degeneration–tau, frontotemporal lobar degeneration–transactive response DNA binding protein 43 (TDP‐43), progressive supranuclear palsy, corticobasal degeneration, dementia with Lewy bodies, multiple system atrophy, cerebral amyloid angiopathy and elderly controls free of pathology. Results Our data suggest that [F‐18]‐AV‐1451 strongly binds to tau lesions primarily made of paired helical filaments in Alzheimer brains (eg, intraneuronal and extraneuronal tangles and dystrophic neurites), but does not seem to bind to a significant extent to neuronal and glial inclusions mainly composed of straight tau filaments in non‐Alzheimer tauopathy brains or to lesions containing β‐amyloid, α‐synuclein, or TDP‐43. [F‐18]‐AV‐1451 off‐target binding to neuromelanin‐ and melanin‐containing cells and, to a lesser extent, to brain hemorrhagic lesions was identified. Interpretation Our data suggest that [F‐18]‐AV‐1451 holds promise as a surrogate marker for the detection of brain tau pathology in the form of tangles and paired helical filament‐tau–containing neurites in Alzheimer brains but also point to its relatively lower affinity for lesions primarily made of straight tau filaments in non‐Alzheimer tauopathy cases and to the existence of some [F‐18]‐AV‐1451 off‐target binding. These findings provide important insights for interpreting in vivo patterns of [F‐18]‐AV‐1451 retention. Ann Neurol 2015 Ann Neurol 2015;78:Ann Neurol 2015;78:679–696